Coffee Product Development Strategy at MSME Jagad Raye Using the Canvas Business Model Method - Erika, Desta Ria (Journal of Agriculture, 2025)
Pagar Alam City in South Sumatra is a prominent centre for Robusta coffee production, with a plantation area of 8,372 hectares and a production output of 22,519 tons in 2021. The region’s coffee has gained recognition nationally and internationally, including participation in Indonesia’s Geographical Indication program and winning the Gourmet Medal at the AVPA event in France. However, despite its potential, local Micro, Small, and Medium Enterprises (MSMEs) such as Jagad Raye continue to face significant challenges, including weak marketing strategies, poorly defined market segmentation, and the lack of structured business planning. These limitations are compounded by the unequal benefits of technological advancements, which tend to favour larger enterprises. To overcome these obstacles, this study employs the Business Model Canvas (BMC) as a strategic framework to analyze and develop Jagad Raye’s coffee product strategy. Using a qualitative descriptive method, data is collected through literature reviews, field observations, and interviews. The study targets consumers aged 15 to 40, particularly the younger segment, who show high interest in coffee innovation, such as fermented coffee. The research highlights the importance of creating strong value propositions, building customer relationships through direct channels like coffee shops, and utilizing digital platforms for distribution and branding. The study concludes that structured planning and innovation, supported by tools like BMC, can help MSMEs remain competitive and sustainable in domestic and global markets.